Chapter Management and governance of the kingdom's finances. Financial literacy as useful knowledge in late-medieval Aragon (1365-1515) - de la Torre Gonzalo, Sandra (Datini Studies in Economic History, 2023)
This paper's primary research question is to what extent change in mechanisms and instruments of financial management proceeding from trading knowledge improved the efficiency of late-medieval poli-ties. To do so, we have examined a territorial state experience in medie-val Iberia. In the mid-14th century, Aragon designed its autonomous fiscal system managed by a kingdom's finance. The new supra-local pol-ity made use of financial accounts to keep track of revenues and to ac-cess credit, which led to the refinement of documentary practice and monitoring methods. The analysis brings up the agency of a group of merchants that shaped the functioning of the Aragonese treasury from budgeting to tax collecting. Particular attention is paid to the impact of the increasing prominence of financial numeracy on institutional ac-countability and governance.